2009
DOI: 10.1097/jnr.0b013e3181a53ea3
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Nursing Intervention Studies Published by Taiwan Nurses Association Between 1954 and 2006

Abstract: This study reviewed historical nursing intervention studies in Taiwan and analyzed results based on sample characteristics, methodology characteristics, and content characteristics. Historical studies were split into four groups, G1970, G1980, G1990, and G2000, based on the decade in which they were published. A comparison was then made to identify significant differences between G2000 and other groups. A total of 103 nursing intervention studies were analyzed in this study. Results included sample characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…There has been an increase over the past 20 years of nurses working with researchers from other disciplines for both TB and EB studies, indicating that multidisciplinary teams are clearly on the rise. This finding is consistent with findings reported by Moody et al () and Yang et al (). Based on the present findings, we recommend, as did Yang et al (), that authors specify more clearly the nature of collaboration and their contributions to the study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…There has been an increase over the past 20 years of nurses working with researchers from other disciplines for both TB and EB studies, indicating that multidisciplinary teams are clearly on the rise. This finding is consistent with findings reported by Moody et al () and Yang et al (). Based on the present findings, we recommend, as did Yang et al (), that authors specify more clearly the nature of collaboration and their contributions to the study.…”
Section: Discussionsupporting
confidence: 94%
“…Moody et al () found that 20% of nursing studies were multidisciplinary. Yang et al () analyzed 103 nursing intervention studies in three scientific journals published in Taiwan after 1969. Findings indicated that multidisciplinary studies increased significantly from 1970 to 2000.…”
Section: Background Of the Studymentioning
confidence: 99%
“…There are several trend analyses published in different fields and periods (e.g., Agustsdottir, Holcombe, Wright, Daffin, & Ogletree, 1995;Goldrick, Baigis, Larsen, & Lemert, 2000;Froggatt, Field, Bailey, & Krishnasamy, 2003;Haylock, 2008;Scholes, 2010;Yang, Liu, Ni, Chang, & Chen, 2009). Moreover, no analyses for trend in neuroscience nursing research are available, and this study seems to be the first.…”
Section: Limitationsmentioning
confidence: 99%